Feasibility study on Temperature Modulated Dynamic Dielectric Analysis - Partridge, Ivana K.; Kazilas, Michalis C. (Cranfield University, 2004)
The project concerned the development of a novel measurement and analysis tool, designed to aid the study of cure in thermosetting polymers. Cure is the irreversible process whereby an initially liquid (unreacted) resin turns into a rubbery solid and eventually into a rigid crosslinked glass. The process usually requires the application of heat to proceed to completion. The changes in structure are reflected in changing mobilities of electrically charged species in the resin and dielectric signals can therefore be used to monitor the progress of cure. In this project, the normal heating–up of the resin was accompanied by a superimposed sinusoidal temperature variation of +/- 1°C. Deconvolution of the resulting dielectric signal into its reversible and irreversible components made it possible to distinguish between the signal contributions arising from the temperature change alone and from those directly contributable to the irreversible chemical chain extension and crosslinking. This proves the original hypothesis put forward in the proposal. The new ideas generated during the course of the project enabled us to obtain significant follow-on funding from the EPSRC. A new dielectric cell has been designed, which will be used in attempting to track particle dispersion in thermosetting nanocomposit